Success Factors in Managing Legacy System Evolution: A Case Study - Huijgens, Hennie; van Deursen, Arie; van Solingen, Rini (2016 IEEE/ACM International Conference on Software and System Processes (ICSSP), 2016)
In this paper, we attempt to understand what contributes to a successful process for managing legacy system evolution. We provide an analysis of a number of key performance indicators such as cost, duration, and defects. By normalizing through function points, we furthermore compare to a larger benchmark. To do so we performed a mixed, retrospective case study on a series of nine software releases and eight single once-only releases, all performing on a single, legacy software system, in a West-European telecom company. We interviewed eleven stakeholders that were closely involved in the subject software releases. As a result, we listed a number of observations from the quantitative and qualitative analysis. We found that a release process that performs above average on cost and duration satisfies stakeholders through fast response and direct value, even when the reliability and availability of the actual system is weak.